HOW COMPANY MANAGE STAKEHOLDER ENGAGEMENT FOR SUSTAINABLE TOURISM DEVELOPMENT IN INDONESIA? - Atmadi, Gayatri (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2019)
The background of this research is that in the past, the increasing trend of mountain climbing in Indonesia has reportedly raised environmental problems, especially regarding the tremendous volume of rubbish left behind mountain climbers. Plastic waste threatens the Indonesia tourism industry in mountain areas. The government stated that the continuously increasing plastic waste threatens to ruin Indonesia's tourism sector. The mineral water industry is one of the government's primary focuses in its plastic waste reduction. As Indonesia's largest plastic-bottled mineral water brand, Aqua is pledging to remove more plastic from the environment than it uses by 2025. The purpose of the research is to get a descriptive analysis of how the company can manage its stakeholder engagement for reducing plastic waste in Indonesia. This research employed a qualitative narrative analysis method with a case study around Aqua?s efforts for reducing plastic waste in Indonesia and data collected from digital media. The principal results of the research show that Aqua made good collaboration between the Trashbag Community Indonesia, The Ministry of Environment and Forestry, and media journalists on the program ?Sapujagad 2017